Textbook of clinical echocardiography - Otto, Catherine M. (Elsevier/Saunders, 2013)
Textbook of Clinical Echocardiography, 5th Edition enables you to use echocardiography to its fullest potential in your initial diagnosis, decision making, and clinical management of patients with a wide range of heart diseases. World-renowned cardiologist Dr. Catherine M. Otto helps you master what you need to know to obtain the detailed anatomic and physiologic information that can be gained from the full range of echo techniques, from basic to advanced.